Politics of infrastructure governance (case study of roads in Mijen Semarang City 2016 – 2018) - Af’idatun Nisak (Central Research Institute for Agriculture (CeRIA), 2022)
In the problems that exist in Mijen Semarang City itself, which later becomes the main discussion related to the construction of road infrastructure, especially city roads, which is one of the problems that can be seen from the study of urban politics. Mijen is the largest area but the least populated in Semarang City, which the author has examined about road infrastructure, especially city roads, because the practice of road construction in Mijen has increased to become an independent city. The research method that the author uses is a qualitative method with a critical political economy type of political economy approach, namely an approach that discusses the relationship between social structure, power structure and historical power relations. The influence of the regime on the allocation of roads in Mijen, if it is related to efforts to develop road infrastructure which is under the authority of the Public Works Department, civil society is still the object for the provision of goods and services needed to achieve prosperity. The results of field interviews can be concluded that the road infrastructure management model in Mijen Semarang City 2016 – 2018 is a democratic regime with a capitalist economy. The regime is the overall system of institutions involved in the economy (government and construction companies) and influence each other with the aim of helping the community to provide the goods and services needed to achieve prosperity. The influence of the regime on the allocation of roads in Mijen, if it is related to efforts to develop road infrastructure which is under the authority of the Public Works Service, civil society is still the object for the provision of goods and services needed to achieve prosperity. So that the suitability of urban political vision and mission with urban reality in Mijen Semarang City 2016 – 2018 is still dynamic.